2016
DOI: 10.1016/j.envpol.2016.06.032
|View full text |Cite
|
Sign up to set email alerts
|

The roles of protein and lipid in the accumulation and distribution of perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) in plants grown in biosolids-amended soils

Abstract: a b s t r a c tThe roles of protein and lipid in the accumulation and distribution of perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) in seven species of plants from biosolids-amended soils were investigated. The PFOS and PFOA root concentration factors (C root /C soil ) ranged from 1.37 to 4.68 and 1.69 to 10.3 (ng/g root )/(ng/g soil ), respectively, while the translocation factors (C shoot /C root ) ranged from 0.055 to 0.16 and 0.093 to 1.8 (ng/g shoot )/(ng/g root ), respectively. The PFOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 51 publications
5
79
4
Order By: Relevance
“…In addition, lipid content of shoots was higher in soybean than in pumpkin. 48,49 This might be the main reason resulting in higher concentrations of SCCPs in planted blank soybean controls.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, lipid content of shoots was higher in soybean than in pumpkin. 48,49 This might be the main reason resulting in higher concentrations of SCCPs in planted blank soybean controls.…”
Section: Resultsmentioning
confidence: 99%
“…68 Several studies have also investigated the uptake of PFASs into crops and earthworms from biosolids application. 6971 In one study, concentration factors for roots relative to soil up to 4.7 and 10.3 were found for PFOS and PFOA, respectively, and all seven plants investigated displayed root concentration factors greater than one. 71 Elevated PFAS concentrations in meat and dairy products has also been reported, 57, 72 suggesting PFAS uptake from biosolids contaminated agriculture is a source of dietary exposure for farm animals.…”
Section: Human Exposure Pathwaysmentioning
confidence: 97%
“…The PFAAs have been detected in fruits, vegetables, grains, and processed food products in Europe (Haug et al 2010;Herzke et al 2013) and North America (Ostertag et al 2009;Schecter et al 2010). Multiple studies have observed uptake and accumulation of PFAAs by plants from soils (Stahl et al 2009(Stahl et al , 2013Lechner and Knapp 2011;Felizeter et al 2012Felizeter et al , 2014Blaine et al 2013Blaine et al , 2014aBlaine et al , 2014bWen et al 2013Wen et al , 2014Wen et al , 2016Krippner et al 2014Krippner et al , 2015Bizkarguenaga et al 2016;Gobelius et al 2017;Navarro et al 2017). The influence of soil organic carbon on plant uptake of PFAAs has been evaluated; % organic carbon is a primary driver in PFAA availability (Blaine et al 2014b;Wen et al 2014;Bizkarguenaga et al 2016).…”
Section: Introductionmentioning
confidence: 99%